(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the ability of the METS-IR index to identify HbA1c ≥ 7% in patients with type 2 diabetes mellitus. Methods: A cross-sectional study was conducted among 189 patients with type 2 diabetes mellitus. Poor glycemic control was defined as HbA1c ≥ 7%. The discriminative ability of METS-IR was assessed using the receiver operating characteristic curve, a 2×2 contingency table, and logistic regression. Results: The proportion of patients with HbA1c ≥ 7% was 36.5%. The optimal METS-IR cutoff in the study sample was 36.46, with an AUC of 0.669, sensitivity of 71.0%, specificity of 60.0%, positive predictive value of 50.5%, and negative predictive value of 78.3%. METS-IR ≥ 36.46 was significantly associated with HbA1c ≥ 7%, with an OR of 3.675 in the univariate model and an OR of 4.053 after multivariable adjustment. The observed AUC of METS-IR was higher than those of BMI, waist circumference, triglycerides, and triglyceride/HDL-C. Conclusion: METS-IR showed moderate ability to identify HbA1c ≥ 7% in patients with type 2 diabetes mellitus.